The Epidermal Growth Factor Receptor Expression in Leptin-Treated Traumatic Oral Ulcer in Rats - Sabreen S. Abed (Journal of Global Pharma Technology, 2016)
Back ground: The injured tissues need to activate their cellular responses in order to restore their normal histological architecture. Leptin has a significant effect on wound healing by enhancing the expression of many biological molecules and cytokines. The present study aimed to evaluate the effect of topical application of recombinant leptin on induced traumatic oral ulcer healing by mean of immunohistochemical localization of EGF-R. Materials and methods: Forty eight male Albino rats with body weight between (200 -270 gm) and age between 2-3 months, were subjected to traumatic ulcer with 8 mm diameter by surgical blade no.15 on the right side of the buccal mucosa. The animals divided into two groups; control group: the ulcer treated daily with sterilized distilled water, the experimental group: the ulcer treated daily with 10µl of 1 µg/ml recombinant leptin. The rats were sacrificed at 3,7,10 days. The specimens were taken for immunohistochemical study to detect the expression of EGF-R in both control and study groups. Results: The present study showed that the recombinant leptin increased the expression of EGF-R in the ulcer area only at 3rd day of ulceration by both epithelial and mesenchymal cells with highly significant differences than control group. Conclusion: leptin accelerated the healing process in oral mucosal ulcer by increase the expression of EGF-R in early healing period than control.Keywords: leptin, Oral mucosa, Ulcer, EGF-R.